Evolution Process of Toppling Deformations in Interbedded Anti-Inclined Rock Slopes - Yibing Ning; Yanjun Shen; Tao Ding; Panpan Xu; Fenghao Duan; Bei Zhang; Bocheng Zhang; John Victor Smith (Applied Sciences, 2025)
Rock slopes exhibiting anti-inclined interbedded strata have widespread distribution and complex deformation mechanisms. In this study, we used a physical model test with basal friction to replicate the evolution process of the slope deformation. Digital Image Correlation (DIC) and Particle Image Velocimetry (PIV) methods were used to capture the variation in slope velocity and displacement fields. The results show that the slope deformation is conducted by bending of soft rock layers and accumulated overturning of hard blocks along numerous cross joints. As the faces of the rock columns come back into contact, the motion of the slope can progressively stabilize. Destruction of the toe blocks triggers the formation of the landslides within the toppling zone. The toppling fracture zones form by tracing tensile fractures within soft rocks and cross joints within hard rocks, ultimately transforming into a failure surface which is located above the hinge surface of the toppling motion. The evolution of the slope deformation mainly undergoes four stages: the initial shearing, the free rotation, the creep, and the progressive failure stages.